Miklós Rózsa's 'double life' : an assessment of Hungarian folksong elements in three of Rózsa's concert hall works - Brand, Frances (Royal Irish Academy of Music, 2017)
Miklós Rózsa (1907 – 1995) is best known for his Hollywood film scores, but in addition to this he also composed many concert hall works, leading to a diverse compositional output and the self-declaration of a ‘double life’, as expressed in the title of his autobiography. This dissertation examines the influence had by Hungarian folksong on Rózsa’s compositional style. Elements assessed are those identified by Belá Bartók (1881 – 1945) in his essays and lectures. Three concert hall works (Thema, Variationen und Finale, Op. 13a; Sonatina for Clarinet Solo, Op. 27; Sonata per Clarinetto Solo, Op. 41) were selected for their varying periods of composition (1933; 1957; 1987), as well as their different compositional genres (orchestral and solo instrumental). In terms of the clarinet works, these were also chosen as the author is a clarinettist. The above mentioned works are motivically analysed, in order to assess whether Rózsa’s Hungarian heritage is seen to have had an influence on their style. The analysis has three main approaches; Form and Phrasing, Melody and Modality, and Rhythm. These are outlined by Bartók in his essays, for both old and new style Hungarian folksong melodies. The rhythmic patterns described by Bartók feature most heavily in all three works, closely followed by the usage of the typically Hungarian modalities. Hungarian folksong form and phrasing features the least, as these works are much larger than the average folksong. Certain themes do have specifically mentioned folksong phrasing. The forms used, namely theme and variations, rondo, and ternary forms, however, do display a folk music element of musical return. Much of the research done prior has focused on Rózsa’s film career, the other side of his ‘double life’. This study contributes to the Miklós Rózsa research base in terms of the Hungarian elemental motivic analysis and discussion of three concert hall works. It also adds to the clarinet research base, with its analysis of perhaps lesser known works in the repertoire, while also creating awareness of these works for future generations of clarinettists.
Keywords: Music; Rózsa, Miklós, 1907-1995; Rózsa, Miklós, 1907-1995